2011
DOI: 10.1177/0954406211404634
|View full text |Cite
|
Sign up to set email alerts
|

Periodic mixed convection of a nanofluid in a cavity with top lid sinusoidal motion

Abstract: Abstract-The periodic mixed convection of a water-copper nanofluid inside a rectangular cavity with aspect ratio of 3 is investigated numerically. The temperature of the bottom wall of the cavity is assumed greater than the temperature of the top lid which oscillates horizontally with the velocity defined as u = u 0 sin (ω t). The effects of Richardson number, Ri, and volume fraction of nanoparticles on the flow and thermal behavior of the nanofluid are investigated. Velocity and temperature profiles, streamli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For water, they are equal to 247.8, 140, and 2.414 × 10 −5 , respectively [29]. However, based on the previous studies by Karimipour et al [30], the aforementioned correlation can be used with confidence for copper-water nanofluids.…”
Section: Governing Equations For Laminar Nanofluidsmentioning
confidence: 98%
“…For water, they are equal to 247.8, 140, and 2.414 × 10 −5 , respectively [29]. However, based on the previous studies by Karimipour et al [30], the aforementioned correlation can be used with confidence for copper-water nanofluids.…”
Section: Governing Equations For Laminar Nanofluidsmentioning
confidence: 98%
“…Also in micro and nanoscales, the particle-based models should be used such as the Lattice Boltzmann Method or molecular dynamics [19][20][21][22][23]. Raisi et al [24] numerically [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the ratio of heat transfer coefficient of nanofluids to that of base fluid decreased as the average temperature of nanofluids was lowered. Karimipour et al [27] numerically investigated the mixed convection of a water-copper nanofluid inside a rectangular cavity. They observed that when Reynolds number is less than one, heat transfer rate is much greater than when Reynolds number is more than one.…”
Section: Introductionmentioning
confidence: 99%